The Role of Marketing Mix in Increasing Consumer Satisfaction with King Queen Fruit Salad - Wibowo, Ageng Tresno; Ariningsih, Endah Pri (JSSH (Jurnal Sains Sosial dan Humaniora), 2025)
The 4P marketing strategy is an approach that can enhance customer satisfaction. While it has been widely used in various food businesses, research on its implementation specifically for fruit salad products remains limited. This study aims to analyze the impact of the 4P strategy—Product, Price, Place, and Promotion—on customer satisfaction at King Queen Fruit Salad. The research employed a quantitative method, surveying 200 respondents selected through purposive sampling. Data analysis was performed using multiple linear regression. The results indicate that the 4P strategy influences customer satisfaction by 69.8%, with the Product variable contributing the most at 49.9%. The remaining 30.2% of customer satisfaction is influenced by other factors.